MARKETING ANALYSIS OF DRY SHELLED CORN IN NADAWAWI VILLAGE, WEST SABU DISTRICT, SABU RAIJUA REGENCY - Djingi, Evamarduard Haba; Bano, Maria; Un, Paulus; Kapa, Maximillian M.J. (Undana Press, 2025)
Corn is one of the main food crops cultivated by the community in Nadawawi Village. The main problem faced by corn farmers in Nadawawi Village, West Sabu District, Sabu Raijua Regency, lies in the marketing process of their corn production. The marketing locations are approximately 7 km away, causing farmers to spend relatively high transportation costs, ranging from IDR 25,000 to IDR 50,000, while also making them highly dependent on marketing institutions such as traders. Therefore, this study aimed to: (1) identify the corn marketing channels in Nadawawi Village, West Sabu District, Sabu Raijua Regency; (2) determine the marketing margin and farmer's share of corn in Nadawawi Village; and (3) determine the level of corn marketing cost efficiency in the study area. The results show that most corn farmers were of productive age, predominantly male, had a relatively low educational level, had more than ten years of farming experience, had small household dependents, and mostly cultivated land areas of less than 0.5 ha. Two marketing channels were identified: channel I, farmers sell directly to consumers, and channel II, farmers sell to retailers, who then sell to consumers. No marketing margin was found in channel I, while the margin in channel II was IDR 3,200/kg. The farmer's share was 100% in channel I and 61% in channel II. Marketing cost efficiency was 7.78% in channel I and 3.16% in channel II, indicating that channel II was the most efficient marketing channel.